A stability police force for the United States : justification and options for creating U.S. capabilities - Kelly, Terrence K.; Jones, Seth G., 1972-; Barnett, James E.; Crane, Keith, 1953-; Davis, Robert C. (Robert Carl); Jensen, Carl.; Rand eBooks (Santa Monica, CA : RAND, 2009)
Establishing security is the sine qua non of stability operations, since it is a prerequisite for reconstruction and development. Security requires a mix of military and police forces to deal with a range of threats from insurgents to criminal organizations. This research examines the creation of a high-end police force, which we call a Stability Police Force (SPF). The study considers what size force is necessary, how responsive it needs to be, where in the government it might be located, what capabilities it should have, how it could be staffed, and its cost. This monograph also considers several options for locating this force within the U.S. government, including the U.S. Marshals Service, the U.S. Secret Service, the Bureau of International Narcotics and Law Enforcement Affairs (INL) in the Department of State, and the U.S. Army's Military Police. The authors conclude that an SPF containing 6,000 people-created in the U.S. Marshals Service and staffed by a "hybrid option," in which SPF members are federal police officers seconded to federal, state, and local police agencies when not deployed-would be the most effective of the options considered. The SPF would be able to deploy in 30 days. The cost for this option would be $637.3 million annually, in FY2007 dollars.
Introduction -- Objectives and Tasks -- Size and Speed of Deployment -- Institutional Capabilities -- Which Agency Should Create and Maintain an SPF? -- Staffing: Standing or Reserve? -- Costing -- Conclusions -- Appendix: Other Headquarters Options.
"RAND Arroyo Center."
Includes bibliographical references (p. 173-183).
Also available on the internet via WWW in PDF format.
Keywords: Auxiliary police -- United States; Electronic books